Odpowiedzi

2010-02-11T19:39:02+01:00
A)x+4y=-2
3x-8y=10

x=-4y-2
3(-4y-2)-8y=10

x=-4y-2
-12y-8y=10

x=-4y-2
-20y=10 II(-20)

x=-4y-2
y=-2

x=-4*(-2)-2
y=-2

x=8-2
y=-2

x=6
y=-2

c)2x+y=9
5x-4y=3

y=-2x+9
5x-4(-2x+9)=3

y=-2x+9
5x+8x-36=3

y=-2x+9
13x=36+3

y=-2x+9
13x=39 I13

x=3
y=-2*3+9

x=3
y=3

d)3x-2y=5
2x-y=4

3x-2y=5
-y=-2x-4 II(-1)

3x-2y=5
y=2x+4

3x-2(2x+4)=5
y=2x+4

3x-4x-8=5
y=2x+4

-x=8+5
y=2x+4

-x=13 II(-1)
y=2x+4

x=-13
y=12*(-13)+4

x=-13
y=-156+4

x=-13
y=-152

e)2x+9y=-9
-3x+3y=8

2x=-9y-9 II2
-3x+3y=8

x=-4,5y-4,5
-3(-4,5y-4,5)+3y=8

x=-4,5y-4,5
13,5y+13,5+3y=8

x=-4,5y-4,5
16,5y=-13,5+8

x=-4,5y-4,5
16,5y=5,5 II16,5

x=-4,5y-4,5
y=0,33

x=-4,5*0,33-4,5
y=0,33

x=-1,49-4,5
y=0,33

x=-5,99
y=0,33







2010-02-11T19:41:46+01:00
A)x+4y=-2
3x-8y=10

{x=-2-4y
{3x-8y=10

3(-2-4y) -8y=10
-6-12y-8y=10
-6-20y= 10 |+6
-20y=16|:(-20)
y=-16/20
y=-⅘

b)x-2y=3
-2+y=0

{x-2y=3
{y=0+2

x-2(2)=3
x-4=3|+4
x=7

c)2x+y=9
5x-4y=3

{y=9-2x
{5x-4y=3

5x-4(9-2x)=3
5x-36+8x=3|+36
13x=39|:13
x=3

d)3x-2y=5
2x-y=4

{3x-2y=5
{2x-y=4 |*(-1)

{3x-2y=5
{-2x+y=-4

{3x-2y=5
{y=-4+2x

3x -2(-4+2x)=5
3x+8-2x=5|-8
x=-3

e)2x+9y=-9
-3x+3y=8

{2x=-9-9y I:2
{-3x+3y=8

{x=-4,5-4,4y
{-3x+3y=8

-3(-4,5-4,5y) +3y=8
13,5+13,5y+3y=8 I-13,5
16,5y=-5,5 I:16,5
y=0,3(3)